Embracing Watershed Politics - Schlager, Edella (University Press of Colorado, 2008)
In Embracing Watershed Politics, political scientists Edella Schlager and William Blomquist provide timely illustrations and thought-provoking explanations of why political considerations are essential, unavoidable, and in some ways even desirable elements of decision making about water and watersheds. With decades of combined study of water management in the United States, they focus on the many contending interests and communities found in America's watersheds, the fundamental dimensions of decision making, and the impacts of science, complexity, and uncertainty on watershed management.